MULTIPLE GIANT CHALAZIA IN HYPERIMMUNOGLOBULINEMIA E SYNDROME: A CASE REPORT: Poster Presentation - Case Report - Resident - Lily Raudah Putri; Florentina Priscilia; Dany Petra Pranata Barus; Annisa Windyani; Muhammad Shafiq Advani; Lukman Edwar (Majalah Oftalmologi Indonesia, 2023)
Introduction : Hyperimmunoglobulinemia E syndrome (HIES) is a rare primary immunodeficiency disorder that manifests as elevated level of serum immunoglobulin E (IgE) higher than 1.000 IU/mL and multisystem disorder characterized by recurrent skin and pulmonary abscesses caused by autosomal dominant or recessive disorder with gene mutation. We present a case of multiple giant chalazion ina patient with HIES. Case Illustration : A 15-year-old boy was referred to Ophthalmology Department with multiple giant lumps on the left eyelid for the last 2 weeks. He had a history of recurrent multiple lumps on the left lower eyelid in the last 1 year. He was diagnosed with HIES since 8 years ago. He had normal visual acuity of both eyes. Multiple giant chalazion were observed on the left upper and lower eyelid. The patient also presented with scalp and neck infection. Laboratory studies showed elevated total serum IgE level of 53,032 IU/mL and eosinophilia. Discussion : Ocular manifestations in HIES patients are not common. Some cases reported chalazia, keratoconus, and blepharitis. Surgical incision drainage was performed in our patient. Medications and surgical intervention had produced only transient improvement. The patient was treated conservatively. Riskof chalazia recurrence remains unknown as reported cases presented with diverse clinical presentation and follow-up serum IgE evaluation is not routinely performed. Conclusion : Recurrent multiple giant chalazia may occur as an ophthalmic feature of HIES. HIES should be considered and investigated in patients presenting with recurrent giant chalazia.